The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14112324
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Photoaging Effect of Rhodiola rosea Fermented by Lactobacillus plantarum on UVA-Damaged Fibroblasts

Abstract: UVA can cause oxidative stress and photoaging of cells. We established a UVA-induced oxidative stress model of human fibroblasts and focused on the antioxidant and anti-photoaging ability of Lactobacillus plantarum fermented Rhodiola rosea. Compared with the unfermented Rhodiola rosea, Lactobacillus plantarum fermented Rhodiola rosea has better DPPH free radical and hydroxyl free radical scavenging ability, significantly reduces the content of reactive oxygen species (ROS), and improves the antioxidant level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…CP promotes hair growth through the Akt/GSK3β/β-catenin signaling pathway . The efficacy of active ingredients in herbs can be increased by in vitro fermentation or in vivo intake of lactic acid bacteria with relevant enzymatic activities. , Here, we observed that compared with nonfermented CP, CP fermented by L. plantarum CCFM1348 significantly stimulated the proliferation of HDPCs (Figure ), increased the expression of β -catenin , VEGF, and IGF-1 , and downregulated TGF-β1, TGF -β2, and DKK-1 (Figures and ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…CP promotes hair growth through the Akt/GSK3β/β-catenin signaling pathway . The efficacy of active ingredients in herbs can be increased by in vitro fermentation or in vivo intake of lactic acid bacteria with relevant enzymatic activities. , Here, we observed that compared with nonfermented CP, CP fermented by L. plantarum CCFM1348 significantly stimulated the proliferation of HDPCs (Figure ), increased the expression of β -catenin , VEGF, and IGF-1 , and downregulated TGF-β1, TGF -β2, and DKK-1 (Figures and ).…”
Section: Discussionmentioning
confidence: 60%
“…13 The efficacy of active ingredients in herbs can be increased by in vitro fermentation or in vivo intake of lactic acid bacteria with relevant enzymatic activities. 23,24 Here, we observed that compared with nonfermented CP, CP fermented by L. plantarum CCFM1348 significantly stimulated the proliferation of HDPCs (Figure 1), increased the expression of βcatenin, VEGF, and IGF-1, and downregulated TGF-β1, TGF-β2, and DKK-1 (Figures 2 and 3). Therefore, we selected L. plantarumCCFM1348 as the most suitable strain for CP fermentation and verified this using a mice model of alopecia.…”
Section: Discussionmentioning
confidence: 81%
“…According to [ 18 ], the DPPH and hydroxyl radical scavenging rates of PF and PW were determined. The determination of total antioxidant capacity was determined with the ABTS and FRAP method total antioxidant capacity test kit, and the experimental procedure was carried out according to the reagent manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, studying the impact of light on skin cells is crucial for the development of skin health care and the treatment of skin diseases. Fibroblasts are the most common connective tissue cells in the body and are frequently used in light studies [78,79]. Studies have revealed that light has a notable effect on the proliferation and differentiation of fibroblasts and can regulate the extracellular matrix produced by them.…”
Section: Frequency and Wavelength Principle Applicationmentioning
confidence: 99%